2013
DOI: 10.1210/jc.2013-1526
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Meal-Stimulated Ghrelin, PYY, CCK Levels and Satiety in Lean Women With Polycystic Ovary Syndrome: Effect of Low-Dose Oral Contraceptive

Abstract: Basal and stimulated hunger and satiety hormones in lean PCOS patients are not different from lean healthy women, except for a lower meal-stimulated ghrelin response. Short-term use of a low-dose oral contraceptive does not have an effect on appetite regulation of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…As for the role of other gastrointestinal peptides in women with PCOS, results are mixed about GIP secretion, while basal and meal-stimulated levels of CCK have been found to be similar in women with PCOS as compared with BMI-matched controls ( 67 , 68 ). Similar basal and postprandial PYY levels in women with PCOS compared with BMI-matched healthy women have also been frequently reported ( 67-70 ).…”
Section: Gut-brain Axis Role In Pcosmentioning
confidence: 99%
“…As for the role of other gastrointestinal peptides in women with PCOS, results are mixed about GIP secretion, while basal and meal-stimulated levels of CCK have been found to be similar in women with PCOS as compared with BMI-matched controls ( 67 , 68 ). Similar basal and postprandial PYY levels in women with PCOS compared with BMI-matched healthy women have also been frequently reported ( 67-70 ).…”
Section: Gut-brain Axis Role In Pcosmentioning
confidence: 99%
“…A total of 20 reports met the inclusion criteria and were included in this study(11, 2441). Since several studies reported the estimates separately according to different categories of BMI (<25 or ≥25), we treated them as from separate studies and incorporated all in the pooling analysis(25, 26, 30, 32, 35, 41).…”
Section: Resultsmentioning
confidence: 99%
“…For 16 included studies(12, 2429, 3134, 36–39, 41), the diagnosis of PCOS was based on the revised 2003 consensus on diagnostic criteria of PCOS by Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group (42). In these studies all PCOS patients met at least 2 of the required 3 criteria as: 1).…”
Section: Resultsmentioning
confidence: 99%
“…There is no study investigating caloric intake in women with PCOS. While several studies have reported decreased meal-stimulated and/or basal ghrelin levels in women with PCOS [6870], there is no convincing evidence for differences in satiety among affected women [68, 69]. …”
Section: Metabolic Phenotype In Pcosmentioning
confidence: 99%